Macromedia Fireworks 8 revealed - Barbara M. Waxer (Thomson Course Technology, 2006)
Get ready to explore all that Fireworks 8 has to offer! Giving you a firm foundation, Macromedia Fireworks 8 Revealed allows you to master concepts on both a technical and artistic level. Begin by examining the concept behind each task-the goal and the necessary features that are involved. Then go in-depth with the objective of your task as you study examples and learn the steps necessary to complete it. Working your way through comprehensive, step-by-step lessons, you'll develop the confidence you need to create eye-catching documents using Fireworks 8